Characteristics of Fishery Industry MSMEs in Takalar Regency that are Resistant to Interferences in Uncertainty Era - Syamsari Syamsari; M Syamsul Maarif; Elisa Anggraeni; Siti Amanah (Journal of Social Science, 2022)
Research Business resilience in micro, small and medium enterprises (MSMEs) is limited in number, especially resilience in facing disturbances in an era of uncertainty. The need for research on business resilience is even higher for SMEs in the fisheries sector in developing countries. MSME business resilience needs to be maintained and improved to get sustainability so that it continues contributing to the economy. The purpose of this study is to find the characteristics of the fisheries sector MSMEs in Takalar Regency which have high resilience to face disturbances in the era of uncertainty. The research location is in Takalar Regency, South Sulawesi, Indonesia, and carried out from August to October 2021. This study uses a descriptive analysis method supported by data from in-depth interviews and questionnaires filled out by 100 MSME entrepreneurs who have run fishing businesses for more than five years. The results of study show that high school graduates dominate the characteristics of MSMEs that have high resilience, the age of the business is more than five years, families dominate the MSME workforce, simple organizational structure, the sources of business capital are a diverse, productive response to disturbances dan have a good performance namely generating wealth that supports resilience and supports the sustainability of MSMEs